The impact of tomato domestication-related alleles on plant development - Pinto, Mayara Caroline Carvalho (2021)
The domestication of plants and animals from wild parents occurred independently in various parts of the world thousands of years ago. During this process, humans selected the characteristics of most interested to them. Therefore, many species have domesticated traits in common. This sort of traits, which can be used to differentiate a wild species from domesticate ones, is termed domestication syndrome. The closest ancestor of tomato (Solanum lycopersicum) is believed to be S. pimpinellifolium, a species with pea-sized fruits. To create the current varieties available for consumption, it was necessary to select traits that would modify both the size and the shape of the fruits. Many genes are involved in these traits and their domesticated alleles are now known. Among the most important genes for weight gain are FRUIT WEIGHT 11.3, a cell size regulator, and FRUIT WEIGHT 2.2, which codes for a cell number regulator. As for genes controlling fruit shape, the SUN, is positive growth regulator, and OVATE, a negative growth regulator. Elongated fruits can be produced by either a gain-of-function allele of SUN or a loss-of-function allele of OVATE. Much is known about the impact of these genes on fruits, but their influence on the whole plant development is not always clear. It is also known that plant hormones are important for the physiological control of plant development. Therefore, in this work we sough to understand the impact of fruit weight genes on shoot and root traits, as well as the influence of fruit shape genes on the expression of hormonal pathways during ovary/fruit development.